2018
DOI: 10.26417/ejfe.v1i1.p11-16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Lecturer' Attitudes towards E-Learning According to Demographic Variables

Abstract: 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…This particular finding could provide new insights into the role of gender on attitudes toward e-learning. Nevertheless, this result contrasts with previously related researches (Bahiti & Farizi, 2018;Bakr, 2011;Bassfar, Z., Rozinah, J., & Merza, 2012;Idris & Osman, 2017). These conflicting results could be interpreted by the fact that educators in MU characterized by some factors that affected their attitudes, including limited technology access, skill, resistant to change and interest.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This particular finding could provide new insights into the role of gender on attitudes toward e-learning. Nevertheless, this result contrasts with previously related researches (Bahiti & Farizi, 2018;Bakr, 2011;Bassfar, Z., Rozinah, J., & Merza, 2012;Idris & Osman, 2017). These conflicting results could be interpreted by the fact that educators in MU characterized by some factors that affected their attitudes, including limited technology access, skill, resistant to change and interest.…”
Section: Discussioncontrasting
confidence: 70%
“…It is generally argued that educators' attitudes, perception, and engagement play the main role in the success of the adoption and integrating technology in the teaching-learning process (Bahiti & Farizi, 2018;Dong & Zhang, 2011;Karaca, Can, & Yildirim, 2013;Onasanya, Shehu, Oduwaiye, & Shehu, 2010;Xhaferi et al, 2018;Yilmaz & Bayraktar, 2014).In this context, this study examined the attitude of academic staff towards e-learning, it also investigated the impact of some demographic characteristics on the tutors' perception and attitudes. Generally, the findings revealed that the academic staff in MU had positive attitudes towards-learning, as they think the adoption of e-learning in MU will positively impact on students' performance and engagement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation